2016
DOI: 10.1371/journal.pone.0151293
|View full text |Cite
|
Sign up to set email alerts
|

Two New Native β-Glucosidases from Clavispora NRRL Y-50464 Confer Its Dual Function as Cellobiose Fermenting Ethanologenic Yeast

Abstract: Yeast strain Clavispora NRRL Y-50464 is able to produce cellulosic ethanol from lignocellulosic materials without addition of external β-glucosidase by simultaneous saccharification and fermentation. A β-glucosidase BGL1 protein from this strain was recently reported supporting its cellobiose utilization capability. Here, we report two additional new β-glucosidase genes encoding enzymes designated as BGL2 and BGL3 from strain NRRL Y-50464. Quantitative gene expression was analyzed and the gene function of BGL2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 45 publications
1
14
0
2
Order By: Relevance
“…From these data it was also possible to estimate the inhibition constant K i = 1.5 mmol L −1 ; accordingly, glucose has a strong competitive inhibition effect on M. thermophila BGL50. For the yeast Clavispora NRRL Y-50464, K i values were approximately 38 and 62 mmol L −1 for two isoforms (Wang et al, 2016), but K i values for β-glucosidase inhibition from other fungi can reach more than 100 mmol L −1 (Riou et al, 1998). For comparison, kinetic values of an M. thermophila β-glucosidase, expressed when the BGL3a gene was cloned in Pichia pastoris (Karnaouri et al, 2013) were K m = 0.39 ± 0.12 mmol L −1 (close to our estimated value) but K i was 0.28 mmol L −1 , lower than for BGL50.…”
Section: Resultsmentioning
confidence: 97%
“…From these data it was also possible to estimate the inhibition constant K i = 1.5 mmol L −1 ; accordingly, glucose has a strong competitive inhibition effect on M. thermophila BGL50. For the yeast Clavispora NRRL Y-50464, K i values were approximately 38 and 62 mmol L −1 for two isoforms (Wang et al, 2016), but K i values for β-glucosidase inhibition from other fungi can reach more than 100 mmol L −1 (Riou et al, 1998). For comparison, kinetic values of an M. thermophila β-glucosidase, expressed when the BGL3a gene was cloned in Pichia pastoris (Karnaouri et al, 2013) were K m = 0.39 ± 0.12 mmol L −1 (close to our estimated value) but K i was 0.28 mmol L −1 , lower than for BGL50.…”
Section: Resultsmentioning
confidence: 97%
“…Until now, two native β-glucosidases from the fungus Clavispora have been described as resistant to 5-HMF, but its activity was not enhanced in presence of the compound. Wang et al (2016) showed that 0.12% furfural and 5-HMF did not affect the activity of these two β-glucosidases.…”
Section: Discussionmentioning
confidence: 87%
“…Expression. When grown on a mixture of glucose and cellobiose, the β-glucosidase activity was induced once glucose was exhausted [17,41]. is indicated that β-glucosidase induction is cellobiose-dependent.…”
Section: Evidence Of β-Glucosidase Productionmentioning
confidence: 99%